2004
DOI: 10.3171/spi.2004.100.1.0013
|View full text |Cite
|
Sign up to set email alerts
|

Anterior correction of cervical kyphotic deformity: effects on myelopathy, neck pain, and sagittal alignment

Abstract: Object. Cervical myelopathy may develop as a result of spinal cord compression with or without deformity. The effect of persistent kyphotic deformity on the ability of the cervical cord to recover following decompressive surgery is not known. Methods. Between 1997 and 2000, a total of 28 patients with progressive myelopathy and kyphotic deformity underwent anterior decompression, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
130
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 35 publications
3
130
1
Order By: Relevance
“…Postoperative kyphosis at a fused cervical motion segment has been reported frequently, especially in uninstrumented anterior fusion [28], with an incidence as high as 27.3% [13]. Sagittal malalignment after ACDF may relate to the cervical instability, postoperative axial pain, and the deterioration of neurological deficit, and may influence the functional recovery [7,12]. The local loss of cervical lordosis may also alter dynamic kinematics of the cervical spine and increase biomechanical stress on the anterior vertebral elements in neighboring segments, thus promoting the progression of degenerative changes in the adjacent segments and deteriorating the long-term clinical outcome [2,18].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative kyphosis at a fused cervical motion segment has been reported frequently, especially in uninstrumented anterior fusion [28], with an incidence as high as 27.3% [13]. Sagittal malalignment after ACDF may relate to the cervical instability, postoperative axial pain, and the deterioration of neurological deficit, and may influence the functional recovery [7,12]. The local loss of cervical lordosis may also alter dynamic kinematics of the cervical spine and increase biomechanical stress on the anterior vertebral elements in neighboring segments, thus promoting the progression of degenerative changes in the adjacent segments and deteriorating the long-term clinical outcome [2,18].…”
Section: Discussionmentioning
confidence: 99%
“…It permits decompression of anterior pathology as well as kyphosis correction with strut grafting [26]. There were some studies of anterior correction of cervical kyphosis via a single anterior approach, after which no postoperative neurological deficit occured [13,26,27]. With the anterior procedure, it is easy to apply a distraction force between vertebral bodies, which provides segmental widening of the disc space to create cervical lordosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the neural foramen is enlarged during kyphosis correction with the anterior procedure, which must be one reason for the reported lack of postoperative neurological deficits. As to correction angles of kyphotic deformity in the cervical spine treated by anterior procedures, Ferch et al [27] reported the preoperative kyphosis was 10°and correction was 11°on average. Herman et al [13] reported that their kyphosis correction was 21°on average.…”
Section: Discussionmentioning
confidence: 99%
“…However, at last follow-up, we did not observe any statistically significant positive correlation between clinical outcome and TCL C2-7. As concerns the influence of lordosis on neurologic recovery, Ferch et al [32] reported on 28 patients with progressive myelopathy and kyphotic deformity, which underwent instrumented ACDF. Improvement in myelopathy scores was significantly associated with a local postoperative lordotic angle of about 4°.…”
Section: Influence Of Cervical Lordosismentioning
confidence: 99%
“…The literature offers some hints that reconstruction of cervical lordosis might be favourable concerning clinical outcome and neurologic recovery [32,70,72,113]. However, the question of any influence of a distinct amount of lordotic realignement following the reconstruction of the multilevel decompressed cervical spine demands further investigation [12].…”
mentioning
confidence: 99%